KEMAMPUAN PENGALAMAN AUDITOR DAN MOTIVASI AUDITOR MEMODERASI PENGARUH DUE PROFESSIONAL CARE PADA KUALITAS AUDIT - Putu Gede Wisnu Permana Kawisana; Ni Luh Putu Mita Miati; Ni Luh Putu Ratna Wahyu Lestari (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2017)
This study aims to obtain empirical evidence regarding the effect of due professional care on audit quality by increasing the experience and motivation of auditors as moderating variables. In due diligence due professional care will be related to the experience and motivation of the auditor, because when the experience and motivation of a large auditor, the auditor's professional due diligence will increase. The population sample in this study were 53 people consisting of the Auditor population at Public Accounting Firm in Bali, the data were collected through questionnaires distributed throughout KAP in Bali. The result of this research can be concluded that there is interaction from two moderation variables to the relationship between Professional Care and Audit Quality. experience variables and auditor motivation proved to strengthen the relationship between due professional care to audit quality.